Course design - Fraida Dubin (Cambridge Univ. Press, 1986)
The book describes the factors which must be considered in constructing courses and materials. They cover: the fact-finding stage, establishing realistic goals, surveying existing programs, realizing goals through instructinal plans, selecting the shape of the syllabus, and considerations involved in constructing communicative curricula and syllabuses